1993
DOI: 10.1159/000462443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prestorage Leukocyte Reduction on Proteins of Platelets Obtained by Apheresis

Abstract: The effect of prestorage leukocyte reduction was evaluated on platelet concentrates (PCs) obtained by apheresis using the ‘surge’ technique. Two hours after collection, the PCs were divided into 2 equal units. One unit was filtered through a Sepacell PL-10a®, producing a filtered PC (FPC). The second unit constituted a non-filtered PC (NFPC). FPCs and NFPCs were stored at room temperature in 1,400-ml CLX® bags on a horizontal agitator up to 7 days. We analyzed platelet samples obtained during storage from NFPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This suggests that as the age of PCs increases, the capacity of platelets to become activated in response to thrombin is reduced. It is therefore not surprising that aggregation in response to low doses (0Á05 U mL À1 ) of thrombin is reduced to 80% of initial values at day 7 (Sarraj-Reguieg et al, 1993). There is also a 50% loss of GPV during storage of PCs for 8 days (Metcalfe et al, 1997), which is not unexpected because GPV exists as a complex with GPIb.…”
Section: Adhesion/aggregationmentioning
confidence: 97%
See 3 more Smart Citations
“…This suggests that as the age of PCs increases, the capacity of platelets to become activated in response to thrombin is reduced. It is therefore not surprising that aggregation in response to low doses (0Á05 U mL À1 ) of thrombin is reduced to 80% of initial values at day 7 (Sarraj-Reguieg et al, 1993). There is also a 50% loss of GPV during storage of PCs for 8 days (Metcalfe et al, 1997), which is not unexpected because GPV exists as a complex with GPIb.…”
Section: Adhesion/aggregationmentioning
confidence: 97%
“…When platelets become activated, there is a conformational change in GPIIb/IIIa (CD41/ CD61), enabling binding of fibrinogen and vWF, a key mechanism in promoting platelet-platelet aggregation. Most studies have shown that expression of GPIIb/IIIa does not alter throughout storage of PCs to days 7-9 (Sarraj-Reguieg et al, 1993;Metcalfe et al, 1997;Ferrer et al, 2000a,b), is similar in PRP, BC or apheresis PC (Metcalfe et al, 1997) and is not influenced by leucodepletion (Boomgaard et al, 1994c(Boomgaard et al, , 1995. However, this provides little information on whether there are any changes in the function of this receptor, i.e.…”
Section: Adhesion/aggregationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixma et al [8] identified glycoproteins from the membrane of platelets. Sarray-Reguieg et al [9] and Snyder et al [lo] analyzed the protein modifications during storage of platelets. Assakawa et al [ll] explored the usefulness of 2-D PAGE for the study of genetic variations of platelet proteins.…”
Section: Introductionmentioning
confidence: 99%